2002
DOI: 10.1103/physrevb.65.115210
|View full text |Cite
|
Sign up to set email alerts
|

Stability of large vacancy clusters in silicon

Abstract: Using a density-functional-based tight-binding method we investigate the stability of various vacancy clusters up to a size of 17 vacancies. Additionally, we compute the positron lifetimes for the most stable structures to compare them to experimental data. A simple bond-counting model is extended to take into account the formation of new bonds. This yields a very good agreement with the explicitly calculated formation energies of the relaxed structures for V 6 to V 14 . The structures, where the vacancies for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
48
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 40 publications
9
48
3
Order By: Relevance
“…This can be explained using simple bond counting arguments: the crystal can reconstruct almost perfectly around a hexavacancy, making all atoms remain fourfold. For smaller clusters, the same calculations [15,16,17] conclude that the most stable configurations occur when atoms are removed sequentially from the hexagonal ring.The ring hexavacancy is known to be a good trap for various impurities, such as carbon, oxygen, and copper atoms [16]. It is reasonable to expect, therefore, that it may also be an efficient trap for self-interstitials.…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…This can be explained using simple bond counting arguments: the crystal can reconstruct almost perfectly around a hexavacancy, making all atoms remain fourfold. For smaller clusters, the same calculations [15,16,17] conclude that the most stable configurations occur when atoms are removed sequentially from the hexagonal ring.The ring hexavacancy is known to be a good trap for various impurities, such as carbon, oxygen, and copper atoms [16]. It is reasonable to expect, therefore, that it may also be an efficient trap for self-interstitials.…”
mentioning
confidence: 78%
“…This can be explained using simple bond counting arguments: the crystal can reconstruct almost perfectly around a hexavacancy, making all atoms remain fourfold. For smaller clusters, the same calculations [15,16,17] conclude that the most stable configurations occur when atoms are removed sequentially from the hexagonal ring.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…The results in ref. [36] also were poorly represented by a simple dangling bond model, and an extended model based on new bond formation due to atomic relaxation was proposed.…”
Section: Vacancy Aggregation In Crystalline Siliconmentioning
confidence: 99%
“…Despite these limitations, notable progress in this area recently has been made. Two series of tight-binding calculations 35,36 recently have shown that the binding energies of vacancy clusters are a non-monotonic function of size, and cannot be expressed simply in terms of nearest-neighbor interactions 32,37 . In ref.…”
Section: Vacancy Aggregation In Crystalline Siliconmentioning
confidence: 99%